Risk factor of preterm labor in the west of iran: a case-control study. - Bahareh Derakhshi; Nader Esmailnasab; Ebrahim Ghaderi; Siroos Hemmatpour (Tehran University of Medical Sciences, 2014)
Prematurity is the most common cause of neonatal death. Risk factors of premature birth can be related with ethnicity and genetic. There is no comprehensive high sample size study in Kurdish ethnicity to determine risk factors related to prematurity. This study evaluated risk factors of preterm labor in Kurdish ethnicity.This case-control study was conducted in 200 preterm infants (case group) and 400 term infants (control group), in Besat Hospital, Sanandaj, Iran, in the year 2012. Data was analyzed using SPSS software and analysis was performed by Chi-square, Mann-Whitney and logistic regression tests.In univariate analysis, mother's own prematurity, history of previous preterm labor, prematurity in the first-degree family members, history of dead children, premature rupture of membranes, multiple pregnancies, overt diabetes, chronic hypertension, preeclampsia and eclampsia, infertility and cervical incompetence had significant relation-ship with preterm labor. However, multivariate analysis results showed that abnormal amniotic fluid, premature rupture of membranes, double and multiple pregnancies, chronic hypertension, family history of premature birth, mothers age over 35 years, and cervical incompetence (P